Nurses' Knowledge Toward Continuous Positive Airway Pressure Machine at Respiratory Isolation Unit - Bareq Hussein Ali, Musaab Majid Abdulwahhab, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: For patients with coronavirus disease(COVID-19), continuous positive airway pressure (CPAP) has been considered as a useful treatment. The goal of CPAP therapy is to enhance oxygenation, relieve breathing muscle strain, and maybe avoid intubation. If applied in a medical ward with a multidisciplinary approach, CPAP has the potential to reduce the burden on intensive care units. Methods: Cross-sectional design was conducted in the ALSHEFAA center for crises in Baghdad. Questionnaire filled by 80 nurses who work in Respiratory Isolation Unit who had chosen by non-probability (purposive) selection collected the data. Then the researcher used an observational checklist to evaluate nurses’ practice. The data was analyzed using descriptive statistics and SPSS. Results: the study found a deficit in nurses’ knowledge and practices regarding using of continues positive airway pressure machine for COVID patients Conclusion: The nurses in this study lacked sufficient knowledge and had a low practice regarding using of continues positive airway pressure machine for COVID patients Recommendations: Special education programs should be carried out for the medical staff and specifically for the nurses who are working in the RCU, to raise their awareness toward using of CPAP machine during infecting with COVID and prevent its complication and how to prevent and manage it. Practice guidelines should be defined and implemented.